Keefektifan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Permainan Engklek untuk Meningkatkan Pemahaman Konsep dan Minat Belajar Siswa Sekolah Dasar - Sriyani, Sriyani; Suryani, Ela (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The purpose of this study was to determine the effectiveness of the problem based learning (PBL) model assisted by crank games to improve understanding of science concepts and interest in learning elementary school students. This study uses a quantitative approach, experimental method with a one group pretest-posttest design. Samples were taken by random or random techniques. This research used questionnaire/questionnaire data collection techniques, observation, interviews and documentation. The data analysis technique used is Normality Test, Homogeneity Test, t-test, Simple Linear Regression Test and N-Gain Test. The results of this study show: 1) There is a difference in the average understanding of elementary school students' concepts using the problem-based learning model assisted by crank games. This is evidenced by the sig count value of 0.001 Ë‚ 0.05. So it can be concluded that there is a significant difference between the quality of learning in the experimental class and the control class. The mean for the experimental class was 90.75, far greater than the average for the control class, 79.50. 2) There is a difference in the average learning interest of elementary school students using the problem-based learning model assisted by crank games. This is evidenced by Sig. (2-tailed) is 0.001 ie 0.001 0.05. So it can be concluded that there is a difference in the use of the problem based learning model with the help of the crank on the interest in learning science for SDIT Insan Kamil students by 78.89%. 3) There is an influence of the problem-based learning model assisted by crank games on the understanding of elementary school students' concepts. This is evidenced by t count = 6.638 Ëƒ t table = 0.468 and a significance value of 0.001 Ë‚ 0.05. So it can be concluded that there is an influence of the problem-based learning model assisted by crank games on increasing the ability to understand elementary school students' concepts. 4) There is an influence of the problem-based learning model assisted by crank games on the learning interest of elementary school students. This is evidenced by the sig value of 0.001 0.05. So it can be concluded that there is an influence from the crank-assisted problem-based learning model on interest in learning science in elementary schools. 5) problem-based learning with the help of cranks can improve elementary school students' understanding of concepts. It is proven that the average score of the experimental class is quite effective, namely 56.6%, while the average score of the control class is less effective, namely 26%. So it can be concluded that the problem-based learning model with the help of cranks in science learning can improve elementary school students' conceptual understanding. 6) The crank-assisted problem-based learning model can increase elementary school students' learning interest. It is proved that the average score of the experimental class is quite effective, namely 58%, while the average score of the control class is less effective, namely 29.6%. So it can be concluded that the problem-based learning model with the help of cranks in science learning can increase elementary school students' learning interest.